How to Measuring Comparative Advantage in International Trade - Nurul Azizah Az Zakiyyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Along with the development of relations between countries, both in the social and economic fields, cooperative relations between these countries are also developing. Southeast Asian countries, for example, agreed to form the ASEAN Community (ASEAN Community) in various economic, social and cultural aspects and political security. Indonesia certainly faces very diverse challenges in fighting for market share which is expected to be a place to sell the goods and services it produces. The purpose of this service is to explain and conduct discussion activities related to how to measure the competitiveness of the market share of Indonesian export products. The method used is a presentation in the form of a webinar using zoom. The results of the dedication show that there were active discussions with the participants and increased enthusiasm of the participants to write scientific papers related to trade competitiveness.